Facile Synthesis of Novel V0.13Mo0.87O2.935 Nanowires With High-Rate Supercapacitive Performance - Jiang, Haishun; Sun, Wenjing; Li, Wenyao; Wang, Zhe; Zhou, Xiying; Wu, Zexing; Bai, Jinbo (Frontiers in Chemistry, 2019)
Binary metal oxides composed of molybdenum–vanadium oxides are promising candidates for supercapacitors. Here, we report the synthesis of one-dimensional V0.13Mo0.87O2.935 nanowires through a facile one-step hydrothermal method. This nanowire presented a high specific capacitance of 394.6 F g−1 (1 mV s−1) as an electrode applied to the supercapacitor. Importantly, this electrode showed a perfect rate capability of 91.5% (2 to 10 A g−1) and a continuous verified outstanding cyclic voltammetry of 97.6% after 10,000 cycles. These superior electrochemical properties make the synthesized V0.13Mo0.87O2.935 nanowires a prospective candidate for high-performance supercapacitors.